Regulation of HIV self‐testing in Malawi, Zambia and Zimbabwe: a qualitative study with key stakeholders. (25th March 2019) - Dacombe, Russell J; Watson, Victoria; Nyirenda, Lot; Madanhire, Claudius; Simwinga, Musonda; Chepuka, Lignet; Johnson, Cheryl C; Corbett, Elizabeth L; Hatzold, Karin; Taegtmeyer, Miriam
Abstract: Introduction: HIV self‐testing (HIVST) is being introduced as a new way for more undiagnosed people to know their HIV status. As countries start to implement HIVST, assuring the quality and regulating in vitro diagnostics, including HIVST, are essential. We aimed to document the emerging regulatory landscape and perceptions of key stakeholders involved in HIVST policy and regulation prior to implementation in three low‐ and middle‐income countries. Methods: Between April and August 2016, we conducted semi‐structured interviews in Malawi, Zambia and Zimbabwe to understand the relationships between different stakeholders on their perceptions of current and future HIVST regulation and the potential impact on implementation. We purposively sampled and interviewed 66 national‐level key stakeholders from the Ministry of Health and the regulatory, laboratory, logistical, donor and non‐governmental sectors. We used a thematic approach to analysis with an inductively developed common coding framework to allow inter‐country comparison of emerging themes. Results: In all countries, the national reference laboratory was monitoring the quality of HIVST kits entering the public sector. In Malawi, there was no legal mandate to regulate medical devices, in Zambia one regulatory body with a clear mandate had started developing regulations and in Zimbabwe the mandate to regulate was overlapping between two bodies. Stakeholders indicated that they had a poor understanding of the process and requirements for HIVST regulation, as well as lack of clarity and coordination between organizational roles. The need for good collaboration between sectors, a strong post‐market surveillance model for HIVST and technical assistance to develop regulators capacity was noted as priorities. Key informants identified technical working groups as a potential way collaboration could be improved upon to accelerate the regulation of HIVST. Conclusion: Regulation of in vitro diagnostic devices, including HIVST, is now being recognized as important by regulators after a regional focus on pharmaceuticals. HIVST is providing an opportunity for each country to develop similar regulations to others in the region leading to a more coherent regulatory environment for the introduction of new devices.